Brand Image as an Economic Asset: Mediating the Effects of Online Customer Reviews, Customer Experience, and Product Quality on Repurchase Intentions of Karung Jantan Clothing Brand - Mahendra, I Wayan Yoga Praditya; Mahyuni, Luh Putu; Deli, Mazzlida Mat; Musa, Sulaiman (International Journal of Economics Development Research (IJEDR), 2025)
This study investigates brand image as an economic asset by analyzing its mediating role in the relationship between online customer reviews, customer experience, and product quality on consumers’ repurchase intentions for the Karung Jantan clothing brand. Recognizing that a strong brand image can enhance customer loyalty, reduce marketing costs, and increase long-term revenue, this research adopts a quantitative approach and analyzes data using the Partial Least Squares (PLS) method with SmartPLS 4.0. The results reveal that brand image does not significantly mediate the effects of online customer reviews and customer experience on repurchase intention. However, brand image significantly mediates the relationship between product quality and repurchase intention, reinforcing its role as an intangible economic asset. Moreover, online customer reviews, customer experience, and product quality all have a positive and significant direct influence on both brand image and repurchase intention. These findings underscore the economic value of investing in brand image and product quality to drive repeat purchases and ensure sustainable business growth.